Pengembangan Media Edukasi Augmented Reality Arthasasih dalam Lontar Turunan Bhatara Manut Sasih di Museum Gedong Kirtya - Ketut Sudiasa; I Gede Partha Sindu; I Nengah Eka Mertayasa (Lembaga Pengembangan Kinerja Dosen, 2026)
The Turunan Bhatara Manut Sasih lontar manuscript is one of Bali’s cultural heritages that contains high philosophical and religious values. However, it is difficult for the public to understand due to the use of Kawi language, Balinese script, and the limited supporting media at the Gedong Kirtya Museum. This study aims to develop an Augmented Reality (AR)-based educational medium that presents the content of the lontar in a visual, interactive, and easily understandable form through the Artha Sasih application. This research employed the Research and Development (R&D) method using the Multimedia Development Life Cycle (MDLC) model, which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. The application was developed using Unity 3D, Vuforia SDK, and Blender 3D. Product testing included black box testing, content expert validation, media expert validation, and user experience evaluation using the User Experience Questionnaire (UEQ). The results show that the Artha Sasih application functions properly, contains valid content, and has an easy-to-use interface and navigation. Based on the UEQ evaluation, the application achieved an “Excellent” category in all assessment aspects. This AR-based educational medium is able to increase visitors’ interest and understanding of the Turunan Bhatara Manut Sasih lontar content and supports the preservation and digitalization of Balinese cultural heritage. Therefore, the Artha Sasih application is considered feasible for use and ready to be implemented at the Gedong Kirtya Museum.